Comparison of percutaneous plate osteosynthesis and retrograde interlocking femoral nail for femur supracondyler fractures - Orhan Başoğlu; Amet Çağrı Uyar; İsmail Daldal; Zafer Şen; İhsan Öz; Yüksel Laçin Avan; Uğur Özdemir; Erkan İnanmaz; Erhan Şükür; Alauddin Kochai; Alper Kurtoğlu (Sakarya Tıp Dergisi, 2022)
Objectives: There is not optimal treatment option for distal femur. Implant failure, delayed union, nonunion and knee stiffness are the most common problem occur after distal femur fractures. The aim of this study is to compare clinical and radiological outcomes of the most used two techniques. Materials and Methods: Sixty-nine patients with distal femur fractures were included in this study. 45 patients (group A) undergone locked-bridge plating and 24 patients (group B) undergone RIMN. Patients were evaluated in terms of duration of union, complications, range of motion and functional results. Functional results were evaluated according to the knee range of motion and Knee Society Score. Results: There were no significant differences between the two groups in terms of demographic characteristics. While the mean union time was 7.2±2.1 months in the percutaneous plate group, it was 6.5±2 months in the RIMN group; however, there was no statistically significant difference between the study groups in terms of duration of bone healing (p=0.125). There was no statistically significant difference in the range of motion between the two groups at the last follow-up (p=0.371). There was no statistically significant difference in the Knee Society Scores between the two groups (p=0.353) too and also there was no statistically significant difference in the incidence of alignment disorders at the last follow-up between the two groups (p=0.791). Conclusion: Both percutaneous plate osteosynthesis with RIMN to treat supracondylar-intercondylar femur fractures, both groups had similar results in terms of duration of union, range of motion, and Knee Society Scores. Furthermore, there were also similar complication rates in both groups. Both techniques can be used safely in the treatment of distal femoral fractures with satisfactory outcomes. Keywords: Distal femur fractures, Percutaneous plate osteosynthesis, Intramedullary nail